Navigating the SAP Data Analysis Landscape: Opportunities and Challenges - Sadasiva Rao Athota (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the opportunities and challenges associated with data analysis using SAP, a leading enterprise resource planning system. It examines how SAP’s comprehensive data integration capabilities, advanced analytics tools, and real-time processing features can revolutionize organizational decision-making and operational efficiency. The article discusses key benefits such as centralized data access, holistic analysis capabilities, and scalability for growing businesses. However, it also addresses significant challenges, including implementation complexity, data quality concerns, potential for data siloing, and the need for specialized skills. The article further outlines strategies for maximizing SAP’s data analysis benefits, focusing on establishing robust data governance practices and strategic implementation planning. By providing a balanced view of SAP’s potential in data analysis, this article aims to guide organizations in leveraging SAP effectively, highlighting the importance of addressing challenges while capitalizing on opportunities to enhance data-driven decision-making and maintain competitiveness in the digital age.